New landscape conceptualization as a guideline for spatial development: a case study from Serbian spatial planning practice - Pihler , Vladimir; Vasiljević, Nevena; Đorđević , Dejan; Bajić, Luka; Dunčić, Dragana (Geographica Pannonica, 2021)
This work is focused on clarification of the basic principles for the establishment of an innovative approach in the field of landscape research through its application in spatial planning documents in Serbia. The question is posed how the practice of considering landscape character, as a reflection of spatial change dynamics, could direct new spatial arrangements based on the development of strategic spatial planning documents. The research is based on analysis undertaken during the elaboration of the “Spatial plan for a special-purpose area The Cultural Landscape of Sremski Karlovci”. The approach taken in the applied conceptual framework is to view landscape character and its functions as the starting point for guiding dynamic interactions in spatial change and it is opposed to the traditional approach of land-use decision making. This work provides the elements for creating a different conceptual framework for spatial planning in Serbia based on landscape conceptualization and as an application model of the European Landscape Convention.